The impact of service quality and consumer trust on customer satisfaction with zalora e-commerce purchase decisions - A.Cut Indah; B .Putu Nina Madiawati (STIE AMKOP, 2023)
This study examined the relationship between customer satisfaction and Zalora's e-commerce purchase decisions. This study used quantitative approach to investigate the topic, and the data analysis techniques used included descriptive analysis and causal correlation research. Using a nonprobability sample technique, 100 respondents, and a purposive sampling strategy, SmartPLS 3.0 was employed for the study. The study's conclusions show that Service Quality has a statistically significant impact on consumers' choices. Consumer trust has a large and favorable impact on purchasing decisions. Customer satisfaction is significantly impacted by purchasing choices. In purchasing decisions, a significant correlation between customer satisfaction and service quality can be seen. Customer happiness is positively and significantly impacted by purchase decisions made by consumers. Keyword— Service Quality; Consumer Trust; Customer satisfaction; Purchasing Decisions